RASI BINTANG DALAM PENENTUAN ARAH MATA ANGIN PERSPEKTIF ILMU FALAK - Ahmad Zulhaj Bimasakti; Andi Muhammad Akmal; Syukur Abu Bakar (Universitas Islam Negeri Alauddin Makassar, 2023)
The main problems in this research are the theory of star constellations, how to determine the direction of the compass with the constellations, and the view of astronomy about the constellations as a guide to the cardinal directions. This type of research is categorized into the type of library research (library research) where the data that is considered relevant in the object of this research is analyzed in depth by the author and then set forth in the form of discussion in answering the problem. In searching for data the author uses data collection methods namely documentation techniques. The results of this study indicate that the constellations that can be used in determining the cardinal directions are the Ursa Major constellation to determine the north direction, the Crux constellation to determine the south direction, the Orion constellation to determine the west direction and the Scorpio constellation to determine the southeast direction. In the view of astronomy that can be used in determining the direction of Qibla, namely the constellation Ursa Major and the constellation Orion. It is hoped that all members of Falakiyah can conduct research on determining the direction of the compass using the constellations. In applying the constellation as one of the methods in determining the cardinal directions, it is necessary to carry out more in-depth research related to the level of accuracy of cardinal directions using star constellations.